Acquired Optic Pits Associated with Laser-assisted In Situ Keratomileusis: A Case Series - Smith, Andrew K (J Curr Glaucoma Pract, 2020)
PURPOSE: To present an association between acquired pits of the optic nerve (APON) and prior laser-assisted in situ keratomileusis (LASIK). MATERIALS AND METHODS: A retrospective case series of patients with an optic disc pit on clinical exam and a history of LASIK. Spectralis Optical Coherence Tomography images and Humphrey Visual Fields were reviewed from prior visits. Extended-depth optical coherence tomography was performed of the optic nerve head at subsequent visits after patients were identified. RESULTS: Seven patients, aged 45–73 years, were identified each with unilateral optic disc pits. Optic disc pits were located inferior in six patients and centrally in one patient. All demonstrated thinning on optical coherence tomography and six patients had corresponding visual field defects. Four patients identified these defects after their LASIK procedure while two patients were unaware of their reproducible visual field defects. All patients were treated with drops initially. One patient underwent laser trabeculoplasty, and three underwent a trabeculectomy after demonstrating progression on maximum tolerated medical therapy. CONCLUSION: This series describes a possible association between LASIK and APON. Given the similarity and severity of vision loss associated with the optic nerve pits in these patients after LASIK, increased awareness and caution is suggested while considering LASIK in susceptible individuals. HOW TO CITE THIS ARTICLE: Smith AK, Bussel I, Ling J, et al. Acquired Optic Pits Associated with Laser-assisted In Situ Keratomileusis: A Case Series. J Curr Glaucoma Pract 2020;14(3):106–108.